Growth and characterization of thin Al-rich AlGaN on bulk GaN as an emitter-base barrier for hot electron transistor. (April 2019) - Prystawko, Pawel; Giannazzo, F.; Krysko, M.; Smalc-Koziorowska, J.; Schilirò, E.; Greco, G.; Roccaforte, F.; Leszczynski, M.
Abstract: In this work, we report on the metal-organic-chemical-vapour-deposition (MOCVD) and characterization of Al-rich thin layers of AlGaN on conductive GaN, to be used as emitter-base barriers for graphene hot electron transistors. After preliminary experiments, aimed to assess the impact of unintentional Ga contaminations on the AlGaN composition, 4.7 nm thick Al0.66 Ga0.33 N films with a 3 nm GaN cap were deposited on the bulk GaN substrate and, for comparison, on a GaN template on sapphire. XRD measurements were employed to evaluate the composition, thickness and fully strained structure state of the ternary AlGaN barrier layers. Atomic force microscopy (AFM) analyses showed a very smooth surface with atomic steps for the AlGaN barrier layer on the bulk crystal, whereas a rougher surface with high density of pits was observed for the films deposited on the GaN/sapphire sample. Finally a graphene heterojunction diode with the Al0.66 Ga0.33 N barrier layer on bulk GaN was fabricated by transfer of CVD grown graphene. Current-voltage characteristics of the diode exhibit very small dependence on the temperature both in forward and reverse polarization, suggesting Fowler-Nordheim (FN) tunneling as the dominant mechanism of current injection from graphene to the AlGaN/GaN two dimensional electron gas (2DEG).